Altered Spontaneous Neural Activity in Peripartum Depression: A Resting-State Functional Magnetic Resonance Imaging Study - Che, Kaili; Mao, Ning; Li, Yuna; Liu, Meijie; Ma, Heng; Bai, Wei; Xu, Xiao; Dong, Jianjun; Li, Ying; Shi, Yinghong; Xie, Haizhu (Frontiers in Psychology, 2020)
Abnormalities related to peripartum depression have been detected in some regions through tasking-state fMRI in the past years. In this study, we used the two markers of resting-state fMRI to investigate changes in spontaneous neural activity and their correlation with the severity of depression. Sixteen individuals with PPD were compared with Sixteen age- and education-matched healthy controls by using rs-fMRI. Two-sample t-test was used to compare the fractional amplitudes of low-frequency fluctuation (fALFF) and regional homogeneity (ReHo) values between groups. The fALFF and ReHo of the abnormal brain region and the Hamilton Depression Scale and Edinburgh Postnatal Depression Scale scores were analyzed. Spontaneous neural activity of the PPD group significantly increased mainly in the left middle frontal gyrus, left precuneus, left inferior parietal lobule, and left dorsolateral prefrontal cortex (DLPFC) and decreased in the bilateral precentral gyrus, the right inferior occipital gyrus compared with those of the HCs. We discovered that the fALFF value of the left DLPFC was negatively correlated with the HAMD score in PPD. This rs-fMRI study suggests that the changed spontaneous neural activity of these regions is related to emotional response. PPD cases with lower fALFF values in the left DLPFC have severe depression.